Tactile recalibration of auditory spatial representations. - Bruns, P; Spence, C; Röder, B (2011)
In the well-known spatial ventriloquism effect, auditory stimuli are mislocalized towards the location of synchronous but spatially disparate visual stimuli. Recent studies have demonstrated a similar influence of tactile stimuli on auditory localization, which predominantly operates in an external coordinate system. Here, we investigated whether this audio-tactile ventriloquist illusion leads to comparable aftereffects in the perception of auditory space as have been observed previously for audiovisual stimulation. Participants performed a relative sound localization task in which they had to judge whether a brief sound was perceived at the same or a different location as a preceding tactile stimulus ("Experiment 1") or to the left or right of a preceding visual stimulus ("Experiment 2"). Sound localization ability was measured before and after exposure to synchronous audio-tactile stimuli with a constant spatial disparity. After audio-tactile adaptation, unimodal sound localization was shifted in the direction of the tactile stimuli during the preceding adaptation phase in both tasks. This finding provides evidence for the existence of an audio-tactile ventriloquism aftereffect and suggests that auditory space (rather than specific audio-tactile connections) can be rapidly recalibrated to compensate for audio-tactile spatial disparities.